Current status of research on the mechanisms of tumor-associated macrophages in esophageal cancer progression - Tang, Yuchao; Shi, Tingting; Lin, Shu; Fang, Taiyong (Frontiers in Oncology, 2024)
Esophageal carcinoma (EC) is one of the most common tumors in China and seriously affects patient survival and quality of life. In recent years, increasing studies have shown that the tumor microenvironment is crucial in promoting tumor progression and metastasis. Tumor-associated macrophages (TAM) are key components of the tumor immune microenvironment and promote both tumor growth and antitumor immunity. Much evidence suggests that TAMs are closely associated with esophageal tumors. However, understanding of the clinical value and mechanism of action of TAM in esophageal cancer remains limited. Therefore, we reviewed the status of research on the role and mechanism of action of TAM in EC progression and summarized its potential clinical application value to provide a theoretical basis for the clinical treatment of EC.